Pengaruh Pengetahuan Pajak, Tarif Pajak, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Bagi Pelaku Usaha Online - Basiroh, Alfi; Sari, Ika (Universitas Gorontalo, 2024)
This study aims to gather empirical evidence on the influence of tax knowledge, tax rates, and tax sanctions on the tax compliance of individual online entrepreneurs in Jabodetabek. This quantitative research employed simple random sampling as the sampling technique, resulting in 97 respondents. Primary data was collected through direct distribution of questionnaires. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using SmartPLS 4.0. The findings revealed that tax knowledge and tax sanctions variables do not significantly influence taxpayer compliance, while the tax rate variable significantly impacts taxpayer compliance.